Прибор для регистрации суточной активности дуплогнездных птиц - Коваль, Н.Ф.; Коваль, С.Л. (Вестник зоологии, 1972)
A simplilled design is suggested for an actograph with a more perfect and reli able contacting device which can be established at the entrance into artificial nests and hollows.